Phonological awareness and phonological working memory in Persian-speaking preschool children with a history of late-talking: A 3-year follow up - Mozhgan Asadi; Farhad Sakhai; Seyed Abolfazl Tohidast; Reyhaneh Jokar; Nasim Masoumi (Acta Psychologica, 2025)
Background: Late-talkers (LTs), defined as toddlers around 2 years of age with limited expressive vocabulary (<50 words) or absence of two-word combinations, are at risk for persistent language disorder. Aims: The aim of this study was investigating phonological awareness (PA) and phonological working memory (PWM) in Persian-speaking children with a history of late-talking (LT) and typically-developing (TD) children aged 5.5 years, and to predict their phonological processing skills using early lexical and morphosyntactic skills at the age of 2.5 years. Methods and procedures: In this longitudinal study, 24 children with a history of LT and 24 TD children, matched for socioeconomic status and age, were assessed using the auditory test of phonological awareness skills (ASHA-5) and the syllable repetition task (SRT). Outcomes and results: Children with a history of LT performed significantly lower than TD peers at 5.5 years on measures of syllable awareness, rhyme awareness, and SRT. Stepwise linear regression analysis showed that early lexical abilities—particularly receptive and expressive vocabulary—were the most important predictors of phonological processing skills at 5.5 years. Conclusions and implications: Children with a history of LT show ongoing challenges in PWM, and possibly subtle vulnerabilities in PA, even in cases where early expressive delays appear to resolve. Given the foundational role of these skills in reading and writing, early identification and targeted preventive interventions are recommended.